OPTIMASI PENGEMBANGAN DIRI DOSEN DALAM MENYIAPKAN SDM DI ERA MEA - Ari Muhardono; Chalimah Chalimah (Fakultas Ekonomi Universitas Pekalongan, 2017)
Along with the development of global market demands, higher education institutions must also continue to make creativity and innovation so that the quality of learning increases, so that the graduates produced have a high competitiveness. To realize the human resources that have competitiveness required the development of self- lecturers. Many factors can affect the self-development of lecturers. This study was conducted with the aim to analyze the influence of work ethic and commitment to self -development of lecturers at Pekalongan Univ ersity (Unikal). In this study, the use of work ethic variables and commitment to analyze the influence of self - development. This research uses multiple regression analysis method. Data obtained from questionnaires that have been inputted online by students in academic information system (SIAKAD) and assessment conducted by Institute of Unique Quality Assurance (LPMU). The results of this study indicate that work ethic variables and commitment variables together significantly influence the self -development of lecturers. Low learner self- development can be improved by encouraging work ethic variables and commitment variables.